Integration of Various Digital Media with Flipped Classroom Models in Chemistry Learning: An Analysis of Student Activities - Paristiowati, Maria; Dianhar, Hanhan; Hasibuan, Nur Azizah Putri; Fitriani, Roisyah (Orbital: Jurnal Pendidikan Kimia, 2024)
This study aims to analyze student activity in flipped learning environments and their response to chemistry learning. The variations of digital media used in this research are YouTube, Miro, Wizer.me, Quizizz, Google Form, and Google Classroom. Participants are 11th grade public high school in Depok city, West Java, Indonesia. The method used is a descriptive qualitative method with data collection techniques through observation sheets, teacher diaries, interviews, reflective journals, and student activity questionnaires. The activity questionnaire in this study used StRIP, adapted from DeMonbrun, et al. Activity indicators consist of two dimensions: student response to instruction and instruction type dimensions. Student activity data is processed using a Likert scale. The results showed that the majority of students responded positively to the second dimension. The results showed that students' responses to instructions and types of instructions developed well during the learning process. This is consistent with the results of the student questionnaire data, which shows a percentage of >70% in each dimension. The affective domain shows that some students have a good attitude of responsibility and discipline. They actively express their opinions and work together in groups. In the psychomotor domain, the students show that they are careful in carrying out and compiling the practicum reports. This study concludes that the flipped classroom learning model using various digital learning media can help develop students' activities in chemistry learning.